Informed Decision Making and Abortion: Crisis Pregnancy Centers, Informed Consent, and the First Amendment. Issue 1 (2015) - Ahmed, Aziza
Abstract : Shifting laws and regulations increasingly displace the centrality of women's needs in the provision of abortion services. Lawmakers and judges contribute to this environment in two ways: by protecting the right of "Crisis Pregnancy Centers" (CPCs) to give false and misleading information about abortion and by supporting legislation mandating that abortion providers give misleading and unnecessary information for the purposes of informed consent. Litigation on informed consent is further complicated through the mobilization of facts — such as the gestational age or sonogram of the fetus — delivered with the intent to dissuade women from accessing abortion. In other words, factual information utilized for ideological purpose. First Amendment litigation has done little to help prioritize women's access to appropriate information about abortion that is calibrated to their needs.